0573 Upper Airway Stimulation Improves Patient Outcome in Moderate to Severe OSA: A Prospective Parallel Trial. (12th April 2019) - Doghramji, Karl; Stevens, Suzane; Strollo, Patrick J; Schwab, Richard S
Abstract: Introduction: Upper airway stimulation (UAS) is an effective therapy for CPAP-intolerant obstructive sleep apnea (OSA) patients. Several single arm studies of UAS have demonstrated reduced OSA severity and improved quality of life. This study enrolled a group receiving UAS and compared them to a control group denied UAS by their insurance plans. Methods: Participants met UAS indications. Baseline sleep study (either home sleep tests (HST) or attended polysomnography) and ESS results were collected from the medical record. Prospective followup HST's were performed in both groups, six months post-operatively in the UAS group, and up to 24 months after enrollment in the control group. Respiratory event index (REI), and Epworth Sleepiness Scale (ESS) and Functional Outcome of Sleep Questionnaire (FOSQ-10) scores were prospectively collected. Results are presented as mean ± SD, p value. Results: 246 Participants in the UAS group, and 58 in the control group, were enrolled. Groups were similar with respect to age and body mass index, yet the proportion of males was higher in the UAS group. Follow-up duration was similar after enrollment (308 ± 141 days vs 287 ± 279, p=0.62). Baseline AHI/REI and ESS scores were similar in both groups, consistent with severe, symptomatic OSA. The UAS group had a larger AHI decrease than the control group (-21.2 ± 16.5 events/hour vs -9.9 ± 16.4 events/hour, p < 0.001). UAS usage was 6.5 ± 1.9 hours/night. UAS group ESS decreased by -5.3 ± 5.6 while the control group ESS increased by 1.6 ± 3.3, p<0.0001. At final visit, FOSQ-10 scores were 17.1 ± 3.2 and 12.5 ± 8.3 in the UAS and control groups, respectively (p < 0.0001). Conclusion: In this prospective study, UAS recipients had a larger reduction in OSA severity and had superior quality of life measures than a similar control group that was denied treatment. Patients awaiting insurance approval for UAS continue to have residual OSA and symptoms, highlighting the need for timely insurance approvals. Support (If Any): Study Sponsored by Inspire Medical Systems